Can there be such a thing as an asian pull? - Charniga, A. (EWF Scientific Magazine, 2016)
An early rise onto the toes with knees flexed, shoulders behind the vertical projection of the bar with excessive bowing of the trunk backward are obvious errors in technique which should preclude a successful outcome. In weightli- fting the outcome of the lifting is determined by the success or failu- re to raise the barbell in the competition exercises within the parame- ters of the technical rules. That is to say, the weightlifter has achieved a successful outcome by overcoming gravity; which, Soviet sport scien- tist I.P. Zhekov noted, does not depend on the form of the barbell's trajectory. Thanks in no small part to the work of many weightlifting sport scientists and countless pro- fessional coaches weightlifting sport has a modern protocol for raising the barbell in the most ef- ficient manner to achieve the desired outcome. The modern protocol of weightlifting technique typically produces a curve-linear bar trajectory known as an 'S' pull. The modern protocol stipulates as well, the optimum disposition of the feet, shins, thighs and trunk to raise the barbell in the most effective manner. A curve - linear bar trajectory in the pulling phases of the snatch and the clean produced with the optimum disposition of feet, shins, thighs and trunk; antithetical to laws of physics, becomes the shortest distance between two points, which as it turns out is not a straight line. "This curve - linear trajectory is connected with the performance of this exercise with the least expen- diture of energy." I,P. Zhekov, 1976 However, bar trajectory aside, the movements of the weightlifter's body as a whole and the individual so - called kinematic links of arms, trunk, thighs, shins and feet deter- mine the outcome of a successful or failed lift.